SERVICE QUALITY TERHADAP KEPUASAN MASYARAKAT MASS RAPID TRANSIT (MRT) DKI JAKARTA DI STASIUN LEBAK BULUS PADA MASA PANDEMIK COVID-19 - Anggi Yuniarti; Toddy Aditya (UNIVERSITAS ISLAM SYEKH YUSUF, 2020)
MRT (Mass Rapid Transit) applies health protocols to prove the serve during a pandemic. It is done to decrease the spread of COVID-19. Service quality is improved to the interests of the society that using the Jakarta MRT. MRT applies the health protocol named BANGKIT (Bersih, Aman, Nyaman, Go Green, Kolaborasi, Inovasi, and Tata Kelola). The research aims to know the satisfaction level towards user society satisfaction as the passenger of Jakarta MRT who rides MRT from Lebak Bulus Station. The researcher used the quantitative method and used Simple random sampling to take the sample. To calculate data, the researcher did a correlation test, linear regression analysis, hypothesis test, and determination coefficient. The result of this research showed that the service quality: reliable responsiveness, assurance, empathy, tangibles significantly had a strong connection towards society satisfaction. The questionnaire which contained 24 questions was valid and reliable because r table value was bigger than r count value and reliable value. The value of r2 determination coefficient was 74.8%. It means service quality (Independent) gave significant effect towards variable of society satisfaction. The researcher could conclude that there was a positive effect given by service quality towards society satisfaction.